2015
DOI: 10.1007/s12275-015-5085-5
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes in human gastric epithelial cells induced by nuclear targeting of Helicobacter pylori urease subunit A

Abstract: Nuclear targeting of bacterial proteins and their pathological effects on host cells are an emerging pathogenic mechanism in bacteria. We have previously reported that urease subunit A (UreA) of Helicobacter pylori targets the nuclei of COS-7 cells through nuclear localization signals (NLSs). This study further investigated whether UreA of H. pylori targets the nuclei of gastric epithelial cells and then induces molecular and cellular changes in the host cells. H. pylori 26695 strain produced and secreted oute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 45 publications
(35 reference statements)
1
17
0
Order By: Relevance
“…Recent reports have revealed that UreA also plays an important and multi‐faceted role for bacteria. There is growing recognition that sub‐unit A contributes to stabilizing the shape of the whole enzyme molecule, and can modulate the activity of urease on a pathway that is not as yet fully understood . It has even been reported that a monoclonal antibody (termed S3) is capable of recognizing the conformational structure of UreA of H .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have revealed that UreA also plays an important and multi‐faceted role for bacteria. There is growing recognition that sub‐unit A contributes to stabilizing the shape of the whole enzyme molecule, and can modulate the activity of urease on a pathway that is not as yet fully understood . It has even been reported that a monoclonal antibody (termed S3) is capable of recognizing the conformational structure of UreA of H .…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that UreA of H . pylori may have an influence on morphological changes in human gastric epithelial cells …”
Section: Discussionmentioning
confidence: 99%
“…The pathogenic role inside the gastroduodenal tract was first described by Marshall and Warren. All infectious strains of H. pylori produce and secrete large quantities of the urease enzyme that allows for colonization of the gastric epithelium, and consequently, neutralizing the acidic environment of the gastric lumen [4,5]. Gastric colonization with H. pylori results stomach chronic gastritis which in most cases will be subclinical.…”
Section: History and Importance Of H Pylorimentioning
confidence: 99%
“…Moreover, probiotics could modulate the host immunologic response via interacting with the epithelial cells, and consequently alter the release of anti-inflammatory effectors, which would leads in a reduction of gastric inflammation [5]. However, the effect of probiotics on the immune response is difficult to simplify, because certain probiotics strains may produce diverse immune responses, which depend on the host's immune status [4].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Promising candidates include proteins in the OMVs. A study of 49 Helicobacter pylori proteins with a nuclear localization signal showed that almost half did traffic to the nucleus (Lee, Jun, Kim, Baik, & Lee, 2015). The V. fischeri OMV proteome has over 200 proteins (Lynch et al, 2019), and three of the proteins have a nuclear localization signal in all of the 13 symbiotic V. fischeri strains that have a full-genome sequence.…”
Section: Introductionmentioning
confidence: 99%